Relationship between Symptoms and Gene Expression Induced by the Infection of Three Strains of Rice dwarf virus - Satoh, Kouji; Shimizu, Takumi; Kondoh, Hiroaki; Hiraguri, Akihiro; Sasaya, Takahide; Choi, Il-Ryong; Omura, Toshihiro; Kikuchi, Shoshi (Public Library of Science, 2011)
We analyzed the gene expression of rice in response to infection with the three RDV strains using a 60-mer oligonucleotide microarray to examine the relationship between symptom severity and gene responses. The number of differentially expressed genes (DEGs) upon the infection of RDV-O, -D84, and -S was 1985, 3782, and 6726, respectively, showing a correlation between the number of DEGs and symptom severity. Many DEGs were related to defense, stress response, and development and morphogenesis processes. For defense and stress response processes, gene silencing-related genes were activated by RDV infection and the degree of activation was similar among plants infected with the three RDV strains. Genes for hormone-regulated defense systems were also activated by RDV infection, and the degree of activation seemed to be correlated with the concentration of RDV in plants. Some development and morphogenesis processes were suppressed by RDV infection, but the degree of suppression was not correlated well with the RDV concentration